Komunikasi Dalam Pengambilan Keputusan Untuk Menangani Keluhan Pelanggan Study kasus Pada PT. Rianti Chemindo Perkasa - Riani, Riska (Universitas Al Azhar Indonesia, 2024)
Management of decision making regarding consumer complaints has a crucial role in maintaining customer satisfaction and building the company's reputation, especially in the car care industry. PT Rianti Chemindo Perkasa, as a company engaged in the production of automotive and industrial chemical products, shows the importance of a holistic and responsive approach to every consumer complaint. This research aims to analyze decision-making management practices regarding consumer complaints at PT Rianti Chemindo Perkasa in the context of car maintenance. The main focus of the research is to understand the approach used by the company, its impact on customer satisfaction, and how these decisions can improve the quality of the company's services. This research uses a descriptive qualitative approach with case studies as the main method. Data was collected through interviews with managers of PT Rianti Chemindo Perkasa, direct observation of management decision-making practices, and analysis of related documents, such as records of complaints and decisions taken. The research results show that PT Rianti Chemindo Perkasa applies a collaborative approach in managing consumer complaints. Decisions are taken jointly involving various departments, such as admin, purchasing and management. Fast and effective response is the main focus, treating every complaint as an opportunity to improve service quality and build strong relationships with customers.